2019
DOI: 10.1002/ejp.1477
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Assessment in Impaired Cognition scale (PAIC15): A multidisciplinary and international approach to develop and test a meta‐tool for pain assessment in impaired cognition, especially dementia

Abstract: Background Over the last decades, a considerable number of observational scales have been developed to assess pain in persons with dementia. The time seems ripe now to build on the knowledge and expertize implemented in these scales to form an improved, “best‐of” meta‐tool. The EU‐COST initiative “Pain in impaired cognition, especially dementia” aimed to do this by selecting items out of existing observational scales and critically re‐assessing their suitability to detect pain in dementia. This paper reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
5
44
0
Order By: Relevance
“…This suggests that training is probably necessary for the rating of items, especially in grading pain with use of several categories of severity. The need for training was also mentioned by healthcare professionals in a survey across Europe (Zwakhalen et al, ) and is planned for the short version of the PAIC scale (Kunz et al, ) for the details of PAIC15 and the associated e‐training).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that training is probably necessary for the rating of items, especially in grading pain with use of several categories of severity. The need for training was also mentioned by healthcare professionals in a survey across Europe (Zwakhalen et al, ) and is planned for the short version of the PAIC scale (Kunz et al, ) for the details of PAIC15 and the associated e‐training).…”
Section: Discussionmentioning
confidence: 99%
“…This idea was recently echoed by a US‐American research group following a similar line of methodological reasoning (Ersek et al, ). Together with results from other psychometric studies, results of the present study will be used in the item reduction process by means of a Delphi procedure, to form the final PAIC‐scale (Kunz et al, ). This is also necessary for feasibility of the measurement scale in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final PAIC collection in its research version (for the clinical version see Kunz, et al, ) is based on items of twelve eligible pain assessment tools which were identified in a comprehensive literature search (Corbett et al, ). Each item had to represent one of three main domains of pain (facial expression, vocalization, body movements) as recommended by the American Geriatric Society (AGS Panel on Persistent Pain in Older Persons, ).…”
Section: Methodsmentioning
confidence: 99%